2000
DOI: 10.1182/blood.v95.4.1465.004k13_1465_1472
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular granzyme A, complexed to proteoglycans, is protected against inactivation by protease inhibitors

Abstract: Granzyme A (GrA) and B (GrB) together with perforin are the main constituents of cytotoxic granules of cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. The cytotoxic proteins are released to deliver a lethal hit during contact between the CTL or NK cell and target cell. With the use of an enzyme-linked immunosorbent assay for antigenic levels, we showed in a recent study that plasma of patients with activated CTLs and NK cells contain elevated levels of extracellular GrA. In this study, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…The contribution of GzmA to the development of joint pathology seems to be independent of perforin. This finding confirms the physiologic relevance of previous studies in which extracellular GzmA was detected in both serum and synovial fluid from humans with RA (17,18). Paralleling the studies in humans, we found that extracellular GzmA was significantly increased in mouse serum and joints in the present studies.…”
Section: Discussionsupporting
confidence: 92%
“…The contribution of GzmA to the development of joint pathology seems to be independent of perforin. This finding confirms the physiologic relevance of previous studies in which extracellular GzmA was detected in both serum and synovial fluid from humans with RA (17,18). Paralleling the studies in humans, we found that extracellular GzmA was significantly increased in mouse serum and joints in the present studies.…”
Section: Discussionsupporting
confidence: 92%
“…The same elution pattern was observed for GzmA and B. This difference in elution pattern at high-and low-salt conditions has been shown previously for GzmA and seems to be typical for proteins complexed to proteoglycans [2,24]. Although the constituents of the macromolecular weight complex detected at physiologic conditions were not determined, results are consistent with previous reports showing that granzymes are packaged in cytotoxic granules being non-covalently bound to proteoglycans, and that these complexes are relatively stable under physiologic conditions but dissociate at high salt concentrations [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…To compare the levels of GzmK with GzmA and B, we additionally analyzed plasma samples from rheumatoid arthritis (RA) patients as well as from patients with viral infections, as these have previously been associated with elevated plasma levels of GzmA and B [2,23]. In RA patients, only GzmA levels were found to be significantly elevated, while plasma levels of GzmB and K were similar to or lower than those of healthy controls (Fig.…”
Section: Detection Of Gzmk In Human Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Any leakage of these cytolytic products from circulating SSRBCs did not appear to induce acute or chronic toxicity likely because granzyme in plasma is degraded by blood borne protease inhibitors antithrombin III and a-2-macroglobulin. 34 Thus, despite their cytolytic properties, mice bearing granzyme and perforin transgenes in their SSRBCs showed durable transgene expression with no untoward acute or chronic effects of these proteins.…”
Section: Dnase I Hypersensitive Site (Hs) Sequences In the Locus Controlmentioning
confidence: 99%